2018
DOI: 10.1038/s41598-018-28019-3
|View full text |Cite|
|
Sign up to set email alerts
|

Cluster-assembled zirconia substrates promote long-term differentiation and functioning of human islets of Langerhans

Abstract: Ex vivo expansion and differentiation of human pancreatic β-cell are enabling steps of paramount importance for accelerating the development of therapies for diabetes. The success of regenerative strategies depends on their ability to reproduce the chemical and biophysical properties of the microenvironment in which β-cells develop, proliferate and function. In this paper we focus on the biophysical properties of the extracellular environment and exploit the cluster-assembled zirconia substrates with tailored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 70 publications
1
44
0
Order By: Relevance
“…We demonstrated that human islets of Langerhans perceive the nanoscale properties of the substrate and activate a mechanotransductive pathway (discussed below), which promotes long-term β-cell survival and function. Interestingly, human islets grown on the nanotopographical substrates (of a certain roughness) maintain glucose-stimulated calcium currents and insulin secretion comparable to those observed in freshly isolated islet, suggesting a crucial role of nanometric topographical signals in shaping β-cell fate in in vitro cultures [64].…”
Section: Topographymentioning
confidence: 72%
See 4 more Smart Citations
“…We demonstrated that human islets of Langerhans perceive the nanoscale properties of the substrate and activate a mechanotransductive pathway (discussed below), which promotes long-term β-cell survival and function. Interestingly, human islets grown on the nanotopographical substrates (of a certain roughness) maintain glucose-stimulated calcium currents and insulin secretion comparable to those observed in freshly isolated islet, suggesting a crucial role of nanometric topographical signals in shaping β-cell fate in in vitro cultures [64].…”
Section: Topographymentioning
confidence: 72%
“…Softer matrices such as hydrogels, chitosan, polylactic-coglycolid (PLGA), and poly-L-lactide (PLA) acids, which better mimic the physiological conditions, instead preserve the islet clustering organization and the β-cell function (reviewed in [54,62,63]). Indeed, when human islets are cultured on soft substrates cell-cell interactions dominate, favoring cell coalescence and preserving the cluster-like organization of the native islet; in contrast, when they are cultured on stiff supports, the extracellular-cell interactions are much stronger, causing cell scattering and the loss of islet-like structure [64].…”
Section: Stiffnessmentioning
confidence: 99%
See 3 more Smart Citations